Long-Term Effects of Social–Emotional Learning on Receipt of Special Education and Grade Retention: Evidence From a Randomized Trial of INSIGHTS. (August 2019) - McCormick, Meghan P.; Neuhaus, Robin; Horn, E. Parham; O'Connor, Erin E.; White, Hope I.; Harding, Samantha; Cappella, Elise; McClowry, Sandee
Social–Emotional Learning (SEL) programs are school-based preventive interventions that aim to improve children's social–emotional skills and behavioral development. Although meta-analytic research has shown that SEL programs can improve academic and behavioral outcomes in the short term, few studies have examined program effects on receipt of special education services and grade retention in the longer term. Using an experimental design, the current study leveraged administrative data available through students' school records (N = 1, 634) to examine the impacts of one SEL program implemented in kindergarten and first grade on receipt of special education and grade retention in fifth grade. The study further considered whether impacts varied for low- versus high-income students. Findings revealed no difference between treatment and control group students in grade retention. However, treatment group students were less likely to ever receive special education services by the end of fifth grade, with low-income students appearing to drive this effect. Implications are discussed.